Transcriptional profiling of arabidopsis tissues reveals the Unique Characteristics of the pollen transcriptome - Becker, J.D. (2010)
Pollen tubes are a good model for the study of cell growth and morphogenesis because of their extreme elongation without cell division. Yet, knowledge about the genetic basis of pollen germination and tube growth is still lagging behind advances in pollen physiology and biochemistry. In an effort to reduce this gap, we have developed a new method to obtain highly purified, hydrated pollen grains of Arabidopsis through flowcytometric sorting, and we used GeneChips (Affymetrix, Santa Clara, CA; representing approximately 8,200 genes) to compare the transcriptional profile of sorted pollen with those of four vegetative tissues (seedlings, leaves, roots, and siliques). We present a new graphical tool allowing genomic scale visualization of the unique transcriptional profile of pollen. The 1,584 genes expressed in pollen showed a 90% overlap with genes expressed in these vegetative tissues, whereas one-third of the genes constitutively expressed in the vegetative tissues were not expressed in pollen. Among the 469 genes enriched in pollen, 162 were selectively expressed, and most of these had not been associated previously with pollen. Their functional classification reveals several new candidate genes, mainly in the categories of signal transduction and cell wall biosynthesis and regulation. Thus, the results presented improve our knowledge of the molecular mechanisms underlying pollen germination and tube growth and provide new directions for deciphering their genetic basis. Because pollen expresses about one-third of the number of genes expressed on average in other organs, it may constitute an ideal system to study fundamental mechanisms of cell biology and, by omission, of cell division.